Teacher Problems in Controversial History Learning in Senior High Schools in Malang City: A Multisites Case Study - Nurhidayati, Waode Yeny; Sayono, Joko (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to identify the problems faced by teachers in teaching history involving controversial events or narratives in Senior High Schools (SMA) in Malang City. Learning history with sensitive issues often poses challenges for teachers from both pedagogical and social aspects. The method used in this study is qualitative with a case study approach according to Robert K. Yin. Data were obtained through interviews and observations in several senior high schools in Malang City. The results of the study indicate that the obstacles faced by teachers include unclear curriculum, lack of training support, and pressure from parents and certain community groups. In addition, students' diverse attitudes towards controversial historical topics are also challenges in creating a conducive learning environment. This study recommends increasing the professional capacity of teachers in managing history learning objectively and critically, as well as the importance of improving the curriculum that supports various perspectives in teaching history.